The Impact of Consumer Perception on Purchase Decision of XL Xtra Combo Lite Data Package Card - Onita Sari Sinaga; Debi Eka Putri; Marto Silalahi (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
The objective of this study was to determine the effect of consumer perception on purchase decision of XL Xtra Combo Lite data package card (a case study of the VI semester students of Management Study Program at the STIE Sultan Agung). This study used the designs of literature review and field research. The type of data used in this study was qualitative and quantitative data. The data sources consisted of primary data and secondary data. The population used in this study was the VI semester students of undergraduate Management Study Program at the STIE Sultan Agung and the sample used was 44 respondents. The data collection was carried out by questionnaire, interview and documentation. The analysis technique used was qualitative descriptive and quantitative descriptive analyses consisting of multiple linear regression, correlation test, as well as determination and hypothesis test. The results of this study concluded that consumer perception and purchase decision were good. Then, for the results of the hypothesis, it was known that consumer perception had a positive and significant effect on the purchase decision of XL Xtra Combo Lite data package card (a case study of the VI semester students of Management Study Program at the STIE Sultan Agung).